Beyond Dualism Between Determinism and Voluntarism in Dynamic Economics, or Essay on the “Paradox of History-creating Decision” - Rozmainsky, I.V. (Економічний вісник Донбасу, 2013)
The paper contains attempt to go beyond dualism between determinism and voluntarism in dynamic economics. On one hand, economic dynamics is not predetermined by tastes, endowments and technologies (as Neoclassical Economics teaches). On the other hand, economic dynamics is not a consequence of absolutely subjective and spontaneous affairs of individuals (as Austrian Economics teaches). In order to solve the problem author applies Post Keynesian approach to the analysis of economic dynamics and emphasizes such conceptions as the principle of “ creative” decision and the principle of shifting equilibrium. He formulates and explores the “ paradox of history-creating decision”. This paradox is the fact that “ uncausedness” and “ creativity” of one decision means inevitably “ causedness” and “ emptiness” of another one. All human decisions cannot be autonomous “ creative”. The different decisions are characterized by the different degrees of “ originativeness” and “ creativeness”. The paper formulates criteria which influence on it.